KEANEKARAGAMAN FAMILI ARTHROPODA TANAH DI KAWASAN HUTAN PENDIDIKAN WANAGAMA KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - Muhammad Muhibbuddin Abdillah; Wuri Handayani; Tatag Bagus Putra Prakarsa (Jurnal Biosilampari : Jurnal Biologi, 2019)
Wanagama Education Forest is the forest made by the ecosystem successions. Wanagama developed on barren hills located at Gunungkidul Province of Yogyakarta Special Region. The succession results providing a new habitat for the wild flora and fauna including soil arthropods. The soil arthropods having an important role in the ecosystem a detritivore etc. This study aimed to knowing soil arthropods diversity at Wanagama. The study conducted at Wanagama Education Forest in December 2017. The soil arthropods collected by six pitch fall trap that was spread at each collection point. Collected specimen by pitch fall trap method then identified and analyzed using diversity, evenness and dominance index. Based on the results, there is 25 family from 13 order of soil arthropods. Based on the data analysis diversity index results are H’=1, 53 and evenness index E=0, 47. The dominant individual is from Formicidae that playing a role as predators at Wanagama. Highest diversity is from Coleoptera order.